Road Story - Van Loon, Julienne (Allen and Unwin, 2005)
Diana Kooper runs from a car crash in the heart of Sydney, scarcely looking back, leaving her best friend, Nicole, slumped and bloody in the damaged vehicle. After hitching a ride to the far west of New South Wales, Diana takes a job as a kitchenhand at Bob's, an isolated truck stop. At first she thinks she can predict the sort of rhythm her life will follow in this dusty, diesel-driven stop, but soon a series of unsettling events disturb the order of things. A dog is brutally stabbed to death and left as a warning beside one of the petrol bowsers. And when Bob rolls his ute in suspicious circumstances, Diana is left to look after the roadhouse kitchen on her own. As every-day life becomes increasingly challenging, Diana struggles with her past and with the ghosts that haunt her present.